Penerapan Algoritma Apriori Korelasi Menentukan Pola Makanan Sehat untuk Balita - Rafli Pramudia; Yani Maulita; Suci Ramadani (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
Children under five are the gold brain generation where brain growth and development is currently developing. The toddler years are a time when children experience rapid growth, a very important period for basic growth to occur which will influence and determine the child's further development. In terms of food consumption, at this age children are still passive consumers, who are not yet able to pick and choose their own food according to their needs, so at this age children are very vulnerable to various health problems if they are malnourished.